Doping purification process of high-purity quartz sand

Through the combination of citric acid and graphene quantum dots, high -purity quartz sand sand is processed, solving the lack of traditional craftsmanship in impurity removal, process complexity and environmental friendship, and realizing high -purity, high -performance quartz sand doping doping Pure is efficient and environmentally friendly.

CN119330361AInactive Publication Date: 2025-01-21TIANCHANG SILICON-BASED NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411251033.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The traditional high-purity quartz sand doping purification process has shortcomings in impurity removal effect, process complexity, cost and environmental friendliness, and it is difficult to meet the challenges of semiconductor chip manufacturing for extremely high purity and performance requirements.

Method used

Citic acid, graphene quantum dots, and other ingredients are used to treat high -purity quartz sand. Through the combination of citric acid and graphene quantum dots, it is controlled by ultrasonic treatment and reaction conditions to achieve the efficient mixing of quartz sand.

Benefits of technology

A significant improvement of the purity, hardness, wear resistance and chemical resistance of quartz sand, shorten the doping time, improve the efficiency and the quality of quartz sand, while reducing the use of chemical reagents and the generation of waste. Good sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330361A_ABST
    Figure CN119330361A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of quartz sand, in particular to a doping purification process of high-purity quartz sand. The method comprises the following steps: step 1, preparing raw materials: preparing high-purity quartz sand raw materials; step 2, citric acid treatment; step 3, adding materials; step 4, controlling reaction conditions; 5, separating and washing: separating the treated quartz sand from the solution, and fully washing; and 6, drying and sintering to obtain a high-purity quartz sand product. In the doping purification process of the high-purity quartz sand, the high-purity quartz sand is treated through the citric acid, the graphene quantum dots and other components, metal impurities in the quartz sand are effectively removed, the purity is remarkably improved, trace metal impurities are further captured and removed, the quartz sand reaches a higher purity standard, and the purity of the quartz sand is improved. The hardness of the quartz sand is improved, the wear resistance of the quartz sand is also improved, and the chemical resistance of the quartz sand is also enhanced, so that the performance stability of the quartz sand is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quartz sand, in particular to a doping and purification process for high-purity quartz sand. Background Art

[0002] With the rapid development of high-tech industries such as semiconductors, optical communications and photovoltaics, the demand for high-purity quartz sand is growing. In semiconductor manufacturing, the production of chips requires extremely high-purity quartz sand as a basic material to ensure the performance and stability of the chips.

[0003] The traditional high-purity quartz sand doping and purification process has many shortcomings. First, it is not very effective in removing impurities. It is difficult to completely remove trace and complex impurities, and it cannot meet the extremely high purity requirements of quartz sand in semiconductor chip manufacturing. Secondly, the process is usually more complicated, which not only requires cumbersome operating steps and professional equipment, but also leads to high costs, limiting its large-scale application. Thirdly, the traditional process performs generally in improving the physical properties of quartz sand. For example, the improvement in properties such as hardness, wear resistance and chemical resistance is limited, and it is difficult to adapt to the complex and changeable environment and process requirements in semiconductor manufacturing. In addition, some traditional processes are not environmentally friendly, and the large-scale use of chemical reagents produces a lot of waste and pollutants, which puts great pressure on the ecology.

[0004] In view of this, there is an urgent need for a bio-based flocculant with high purity, high hardness, high wear resistance and high chemical resistance and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a doping and purification process for high-purity quartz sand to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides a doping and purification process for high-purity quartz sand, comprising the following steps:

[0007] S1.1, Raw material preparation: prepare high-purity quartz sand raw materials;

[0008] S1.2, citric acid treatment: mix quartz sand with citric acid solution and soak for 1-24h;

[0009] S1.3, material addition: add graphene quantum dots to the quartz sand treated with citric acid and perform ultrasonic treatment to fully combine the graphene quantum dots with citric acid, then add other ingredients, use a stirring device to ensure uniform dispersion, and react;

[0010] S1.4. Reaction condition control: Control the temperature, time and pH conditions of the reaction to optimize the doping and purification process.

[0011] S1.5, separation and washing: separate the treated quartz sand from the solution and wash it thoroughly.

[0012] S1.6, Drying and sintering: The purified quartz sand is dried and sintered to obtain high-purity quartz sand products.

[0013] As a further improvement of the technical solution, in S1.2, the citric acid extraction technology comprises the following steps:

[0014] S2.1. Raw material preparation: Select fruits rich in citric acid, wash and peel them, and remove seeds and other impurities;

[0015] S2.2, crushing and pressing: crush the prepared fruit into small pieces, and then use pressing equipment and methods to squeeze out the juice from the fruit;

[0016] S2.3, precipitation and filtration: add a precipitant to the squeezed juice to precipitate the impurities therein; then filter it to obtain a relatively clear filtrate.

[0017] S2.4, Neutralization: Slowly add a neutralizing agent to the filtrate to convert the citric acid therein into calcium citrate precipitate;

[0018] S2.5, acid hydrolysis: reacting the calcium citrate precipitate with a strong acid to convert the calcium citrate back into a citric acid solution;

[0019] S2.6, Ion exchange and decolorization: The solution obtained by acid hydrolysis is passed through an ion exchange resin to remove metal ions and other impurities; at the same time, a decolorizing agent such as activated carbon is used for decolorization to improve the purity and color of the citric acid solution.

[0020] S2.7, Concentration and crystallization: Use the evaporation concentration method to gradually evaporate the water in the citric acid solution to increase its concentration; when the solution reaches a supersaturated state, citric acid will crystallize out.

[0021] S2.8, separation and drying: the crystallized citric acid is separated from the mother liquor by filtration, and then the crystals are dried to obtain a pure citric acid solid product.

[0022] As a further improvement of the technical solution, in S1.2, the amount of citric acid used is 2wt%-12wt% of the mass of quartz sand.

[0023] As a further improvement of the present technical solution, in S1.3, the amount of the graphene quantum dots is 0.2wt%-1.2wt% of the mass of the quartz sand, and the amount of the other components is 0.1wt%-1wt% of the mass of the quartz sand.

[0024] As a further improvement of the technical solution, in S1.3, the other components include the following components:

[0025] Surfactants, chelating agents, acids and precipitants.

[0026] As a further improvement of the technical solution, the surfactant includes sodium dodecyl sulfate and hexadecyltrimethylammonium bromide.

[0027] As a further improvement of the technical solution, the chelating agent includes ethylenediaminetetraacetic acid and diethylenetriaminepentaacetic acid.

[0028] As a further improvement of the present technical solution, the acid includes hydrofluoric acid.

[0029] As a further improvement of the present technical solution, the precipitant includes lime milk.

[0030] As a further improvement of the technical solution, the amount of citric acid is 8wt% of the mass of quartz sand, the amount of graphene quantum dots is 0.9wt% of the mass of quartz sand, and the amount of other components is 0.6wt% of the mass of quartz sand.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. In the doping and purification process of high-purity quartz sand, high-purity quartz sand is treated with citric acid, graphene quantum dots and other ingredients to effectively remove metal impurities in the quartz sand and significantly improve the purity. In addition, trace metal impurities are further captured and removed to make the quartz sand reach a higher purity standard, which not only improves the hardness of the quartz sand, but also improves the wear resistance of the quartz sand and enhances the chemical resistance of the quartz sand, thereby ensuring the stability of its performance.

[0033] 2. In the doping and purification process of high-purity quartz sand, the speed of adsorption and surface chemical reaction is accelerated through the secondary combination of graphene quantum dots and citric acid, which greatly shortens the time of doping and purification and improves the work efficiency of quartz sand doping and purification. In addition, the emulsification and dispersing effect of the surfactant makes the quartz sand particles evenly dispersed, increases the contact area with the purification agent, improves the efficiency of impurity removal, and thus improves the quality of quartz sand.

[0034] 3. In the doping and purification process of high-purity quartz sand, citric acid is extracted from common fruits. The raw materials are widely available and the cost is relatively low. The entire doping and purification process is relatively environmentally friendly, reducing the use of chemical reagents and the generation of waste, reducing the pressure on the environment, and reducing interference and damage to the ecosystem, which helps maintain ecological balance and protect environmental quality, thus having good sustainability. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a flowchart of the doping and purification process of high-purity quartz sand of the present invention;

[0036] Figure 2 It is a flowchart of citric acid extraction of the present invention;

[0037] Figure 3 This is a block diagram of the amount of each raw material used in Examples 1-3 of the present invention;

[0038] Figure 4 It is a block diagram of the detection indicators of each sample in Examples 1-3 of the present invention and the reference example. DETAILED DESCRIPTION

[0039] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0040] according to Figure 1 and Figure 2 As shown, the embodiment of the present invention also provides a doping and purification process for preparing the above-mentioned high-purity quartz sand, and the specific steps are as follows:

[0041] Step 1: Raw material preparation: Prepare high-purity quartz sand raw materials to ensure that its impurity content is low;

[0042] Step 2: Citric acid treatment: Mix and soak the quartz sand with citric acid solution for 1-24 hours. Citric acid can form complexes with some metal ions, which helps to remove impurities.

[0043] Step 3, material addition: add graphene quantum dots to the quartz sand treated with citric acid for ultrasonic treatment, so that the graphene quantum dots are fully combined with citric acid, and then add other ingredients, use a stirring device to ensure uniform dispersion, and react. Graphene quantum dots have special physical and chemical properties and may interact with the surface of quartz sand to improve the doping and purification effect. Other ingredients can enhance the purification effect;

[0044] Step 4: Control reaction conditions: Control the temperature, time and pH conditions of the reaction to optimize the doping and purification process.

[0045] Step 5: Separation and washing: Separate the treated quartz sand from the solution and wash it thoroughly to remove residual impurities and chemical reagents.

[0046] Step 6: Drying and sintering: Drying and sintering the purified quartz sand to obtain high-purity quartz sand products.

[0047] The present invention adopts the following ingredients:

[0048] The amount of citric acid is 2wt%-12wt% of the mass of quartz sand, the amount of graphene quantum dots is 0.2wt%-1.2wt% of the mass of quartz sand, and the amount of other components is 0.1wt%-1wt% of the mass of quartz sand, wherein: the other components include the following components:

[0049] Surfactants include sodium dodecyl sulfate and hexadecyl trimethyl ammonium bromide, which have good emulsifying and dispersing effects, can help disperse the quartz sand particles so that they can be more fully contacted with the purification reagents, and can also improve the surface properties of the quartz sand and improve the efficiency of impurity removal;

[0050] Chelating agents include ethylenediaminetetraacetic acid and diethylenetriaminepentaacetic acid, which can form stable chelates with a variety of metal ions and help remove metal impurities;

[0051] Acids include hydrofluoric acid, which can effectively remove silicon oxides and some metal oxides from the surface of silica;

[0052] The precipitant includes lime milk, which precipitates some of the impurity ions.

[0053] Further, in order to help remove trace metal impurities in quartz sand, therefore, in step 2, the citric acid extraction technology includes the following steps:

[0054] Step 1: Prepare the raw materials: Choose fruits rich in citric acid, such as lemons, oranges, tangerines, etc. Wash and peel these fruits, and remove seeds and other impurities;

[0055] Step 2: Crushing and squeezing: crush the prepared fruit into small pieces, and then use squeezing equipment and methods, such as a juicer, to squeeze the juice out of the fruit;

[0056] Step 3: Sedimentation and filtration: Add a precipitant, such as lime milk, to the squeezed juice to precipitate the impurities therein; then remove the precipitate and other solid impurities through filtering operations, such as using filter paper or filtering equipment, to obtain a relatively clear filtrate.

[0057] Step 4: Neutralization: Slowly add a neutralizing agent, such as calcium hydroxide or other suitable neutralizing agent, to the filtrate to convert the citric acid therein into calcium citrate precipitate;

[0058] Step 5: Acid hydrolysis: react the calcium citrate precipitate with a strong acid, such as sulfuric acid or hydrochloric acid, to convert the calcium citrate back into a citric acid solution;

[0059] Step 6: Ion exchange and decolorization: The solution obtained by acid hydrolysis is passed through an ion exchange resin to remove metal ions and other impurities therein; at the same time, a decolorizing agent such as activated carbon is used for decolorization to improve the purity and color of the citric acid solution.

[0060] Step 7, concentration and crystallization: Use evaporation concentration method to gradually evaporate the water in the citric acid solution to increase its concentration; when the solution reaches a supersaturated state, citric acid will crystallize out.

[0061] Step 8, separation and drying: The crystallized citric acid is separated from the mother liquor by filtration, and then the crystals are dried, usually at low temperature, to obtain a pure citric acid solid product.

[0062] In the present invention, firstly, the graphene quantum dots and citric acid are combined, which can not only improve the purity of quartz sand and enhance the dispersibility, but also change the physical properties of quartz sand, such as hardness, wear resistance and chemical resistance, so that the quartz sand is more stable and reliable under harsh environments such as high temperature and high pressure. At the same time, the graphene quantum dots and citric acid are combined for a second time. The citric acid molecules contain functional groups such as carboxyl groups, which can react with functional groups on the surface of the graphene quantum dots to form chemical bonds. Moreover, the graphene quantum dots have a conjugated structure, and π electrons can have a π-π stacking effect with the aromatic rings in the citric acid molecules to enhance the combination between the two. The carboxyl groups and hydroxyl groups in the citric acid molecules can form hydrogen bonds with the functional groups on the surface of the graphene quantum dots to further stabilize the combination, thereby effectively improving the doping purification speed and removal efficiency of the quartz sand.

[0063] By treating high-purity quartz sand with citric acid, graphene quantum dots and other ingredients, the metal impurities in the quartz sand can be effectively removed, significantly improving the purity. In addition, trace metal impurities can be further captured and removed to make the quartz sand reach a higher purity standard, which not only improves the hardness of the quartz sand, but also improves the wear resistance of the quartz sand and enhances the chemical resistance of the quartz sand, thereby ensuring the stability of its performance.

[0064] Through the secondary combination of graphene quantum dots and citric acid, the speed of adsorption and surface chemical reaction is accelerated, the time of doping and purification is greatly shortened, and the work efficiency of quartz sand doping and purification is improved. In addition, the emulsification and dispersion effect of the surfactant makes the quartz sand particles evenly dispersed, increasing the contact area with the purification agent, improving the efficiency of impurity removal, and thus improving the quality of quartz sand.

[0065] Citric acid is extracted from common fruits. The raw materials are widely available and the cost is relatively low. The entire doping and purification process is relatively environmentally friendly, reducing the use of chemical reagents and the generation of waste, reducing pressure on the environment, and reducing interference and damage to the ecosystem, which helps maintain ecological balance and protect environmental quality, thus having good sustainability.

[0066] According to different raw material dosages, the doping and purification of high-purity quartz sand provided by the present invention is further illustrated by the following specific examples.

[0067] Example 1

[0068] High-purity quartz sand is doped and purified by using citric acid in an amount of 2wt% of the mass of the quartz sand, graphene quantum dots in an amount of 0.2wt% of the mass of the quartz sand, and other components in an amount of 0.1wt% of the mass of the quartz sand.

[0069] Mix and soak the quartz sand with the citric acid solution for 10-12 hours. Then, add graphene quantum dots to the citric acid-treated quartz sand for ultrasonic treatment to fully combine the graphene quantum dots with the citric acid. Then, add other ingredients, use a stirring device to ensure uniform dispersion, and react. Control the reaction conditions such as temperature, time and pH value to optimize the doping purification process. Then, separate the treated quartz sand from the solution and wash it thoroughly. Finally, dry and sinter the purified quartz sand to obtain a high-purity quartz sand product.

[0070] Example 2

[0071] High-purity quartz sand is doped and purified by using 8wt% of citric acid, 0.9wt% of graphene quantum dots and 0.6wt% of other components based on the mass of the quartz sand.

[0072] Mix and soak the quartz sand with the citric acid solution for 6-8 hours. Then, add graphene quantum dots to the citric acid-treated quartz sand for ultrasonic treatment to fully combine the graphene quantum dots with the citric acid. Then, add other ingredients, use a stirring device to ensure uniform dispersion, and react. Control the reaction conditions such as temperature, time and pH value to optimize the doping and purification process. Then, separate the treated quartz sand from the solution and wash it thoroughly. Finally, dry and sinter the purified quartz sand to obtain a high-purity quartz sand product.

[0073] Example 3

[0074] High-purity quartz sand is doped and purified by using citric acid in an amount of 12wt% of the mass of the quartz sand, graphene quantum dots in an amount of 1.2wt% of the mass of the quartz sand, and other components in an amount of 1wt% of the mass of the quartz sand.

[0075] Mix and soak the quartz sand with the citric acid solution for 4-6 hours. Then, add graphene quantum dots to the citric acid-treated quartz sand for ultrasonic treatment to fully combine the graphene quantum dots with the citric acid. Then, add other ingredients, use a stirring device to ensure uniform dispersion, and react. Control the reaction conditions such as temperature, time and pH value to optimize the doping and purification process. Then, separate the treated quartz sand from the solution and wash it thoroughly. Finally, dry and sinter the purified quartz sand to obtain a high-purity quartz sand product.

[0076] Table 1 Amount of each raw material used in Examples 1-3 (wt%)

[0077] Example 1 Example 2 Example 3 Citric Acid 2 8 12 Graphene quantum dots 0.2 0.9 1.2 Other Ingredients 0.1 0.6 1

[0078] In order to verify that the high-purity quartz sand prepared in the embodiment of the present invention has good wear resistance and purity standardization, the doping and purification of the high-purity quartz sand provided in the embodiment of the present invention is described through the following test examples.

[0079] Test example

[0080] The purpose of this test example is to explore the effects of different component ratios on the doping and purification of high-purity quartz sand.

[0081] Test objective: To detect the purity, hardness, wear resistance, chemical resistance and impurity removal efficiency of the high-purity quartz sand after doping and purification of the present invention.

[0082] Experimental method: Experimental group A, experimental group B and experimental group C respectively adopted the high-purity quartz sand doped and purified component ratios provided in Examples 1-3; the control example adopted control group A and control group B, wherein: control group A was treated with citric acid only, the amount was 2wt% of the mass of quartz sand, there were no graphene quantum dots and other components, only citric acid was used for treatment, and the immersion time was the same as that of experimental example A; control group B used a conventional chemical purification method.

[0083] Specific detection indicators are shown in Table 2.

[0084] Table 2 Test indicators of each sample

[0085] Experimental Example A Experimental Example B Experimental Example C Comparative Example A Comparative Example B purity(%) 95 99 98 90 80 Hardness (Mohs) 8 9 8.5 6.5 6 Wear resistance (% improvement) 30 60 50 10 5 Chemical resistance (% enhancement) 40 70 60 20 10 Impurity removal efficiency (%) 80 92 90 60 50

[0086] according to Figure 3 , Figure 4As shown in Table 2, in general, Example B performs well in various indicators. Its purity reaches 99%, hardness is 9 (Mohs), wear resistance is improved by 60%, chemical resistance is enhanced by 70%, and impurity removal efficiency is 92%; in contrast, Example A has a purity of 95%, a hardness of 8 (Mohs), wear resistance is improved by 30%, chemical resistance is enhanced by 40%, and impurity removal efficiency is 80%; Example C has a purity of 98%, a hardness of 8.5 (Mohs), wear resistance is improved by 50%, chemical resistance is enhanced by 60%, and impurity removal efficiency is 90%; Control Example A is treated with only 2wt% citric acid, and various properties are significantly weaker, and Control Example B uses conventional chemical purification methods, and the effect is even worse.

[0087] Because the higher dosage of citric acid, graphene quantum dots and other components in Example B makes the synergy between them more sufficient, it can more effectively remove impurities and improve the physical properties of quartz sand. Although the dosage of the components in Experimental Example C is the highest, its effect is not the best. The excessive dosage of the components will lead to some adverse reactions, and the excessive dosage of the components will increase the cost, while the performance improvement is not enough to compensate for the increase in cost.

[0088] In summary, the use of the component ratio of Example B for doping and purification of high-purity quartz sand is better than that of Example A and Example C in terms of purity, hardness, wear resistance, chemical resistance and impurity removal efficiency, and can more effectively improve the quality of quartz sand.

[0089] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A doping and purification process for high-purity quartz sand, characterized in that: The following steps are involved: S1.1, Raw material preparation: prepare high-purity quartz sand raw materials; S1.2, citric acid treatment: mix quartz sand with citric acid solution and soak for 1-24h; S1.3, material addition: add graphene quantum dots to the quartz sand treated with citric acid and perform ultrasonic treatment to fully combine the graphene quantum dots with citric acid, then add other ingredients, use a stirring device to ensure uniform dispersion, and react; S1.

4. Reaction condition control: Control the temperature, time and pH conditions of the reaction to optimize the doping and purification process. S1.5, separation and washing: separate the treated quartz sand from the solution and wash it thoroughly. S1.6, Drying and sintering: The purified quartz sand is dried and sintered to obtain high-purity quartz sand products.

2. The doping and purification process of high-purity quartz sand according to claim 1, characterized in that: In S1.2, the citric acid extraction technique comprises the following steps: S2.

1. Raw material preparation: Select fruits rich in citric acid, wash and peel them, and remove seeds and other impurities; S2.2, crushing and pressing: crush the prepared fruit into small pieces, and then use pressing equipment and methods to squeeze out the juice from the fruit; S2.3, precipitation and filtration: add a precipitant to the squeezed juice to precipitate the impurities therein; then filter it to obtain a relatively clear filtrate. S2.4, Neutralization: Slowly add a neutralizing agent to the filtrate to convert the citric acid therein into calcium citrate precipitate; S2.5, acid hydrolysis: reacting the calcium citrate precipitate with a strong acid to convert the calcium citrate back into a citric acid solution; S2.6, Ion exchange and decolorization: The solution obtained by acid hydrolysis is passed through an ion exchange resin to remove metal ions and other impurities; at the same time, a decolorizing agent such as activated carbon is used for decolorization to improve the purity and color of the citric acid solution. S2.7, Concentration and crystallization: Use the evaporation concentration method to gradually evaporate the water in the citric acid solution to increase its concentration; when the solution reaches a supersaturated state, citric acid will crystallize out. S2.8, separation and drying: the crystallized citric acid is separated from the mother liquor by filtration, and then the crystals are dried to obtain a pure citric acid solid product.

3. The doping and purification process of high-purity quartz sand according to claim 1, characterized in that: In S1.2, the amount of citric acid used is 2wt%-12wt% of the mass of quartz sand.

4. The doping and purification process of high-purity quartz sand according to claim 1, characterized in that: In S1.3, the amount of the graphene quantum dots is 0.2wt%-1.2wt% of the mass of the quartz sand, and the amount of the other components is 0.1wt%-1wt% of the mass of the quartz sand.

5. The doping and purification process of high-purity quartz sand according to claim 1, characterized in that: In S1.3, the other ingredients include the following ingredients: Surfactants, chelating agents, acids and precipitants.

6. The doping and purification process of high-purity quartz sand according to claim 5, characterized in that: The surfactants include sodium lauryl sulfate and cetyltrimethylammonium bromide.

7. The doping and purification process of high-purity quartz sand according to claim 5, characterized in that: The chelating agents include ethylenediaminetetraacetic acid and diethylenetriaminepentaacetic acid.

8. The doping and purification process of high-purity quartz sand according to claim 5, characterized in that: The acids include hydrofluoric acid.

9. The doping and purification process of high-purity quartz sand according to claim 5, characterized in that: The precipitating agent includes milk of lime.

10. The doping and purification process of high-purity quartz sand according to claim 1, characterized in that: The amount of citric acid used is 8wt% of the mass of quartz sand, the amount of graphene quantum dots used is 0.9wt% of the mass of quartz sand, and the amount of other components used is 0.6wt% of the mass of quartz sand.

Citation Information

Patent Citations

  • Preparation method of low-hydroxyl ultrahigh-purity quartz sand

    CN107445173A

  • Purification method of high purity quartz sand tailings

    CN110510620A

  • Preparation method of high-purity quartz sand

    CN110665631A

  • Improvements in the purification of citric acid

    GB905817A

  • Method for manufacturing high-purity silicon material

    US20100233063A1